2020
DOI: 10.1109/tvcg.2019.2934284
|View full text |Cite
|
Sign up to set email alerts
|

Color Crafting: Automating the Construction of Designer Quality Color Ramps

Abstract: Fig. 1. Our approach uses design mining and unsupervised clustering techniques to produce automatically generated color ramps that capture designer practices. The four choropleth maps shown above utilize color ramps generated from our approach. Developers select a single guiding seed color, shown in the squares below each map, to generate a ramp. We then fit curves capturing structural patterns in designer practices in CIELAB (bottom) to these seed colors to generate ramps (middle, seed colors indicated by a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 77 publications
0
42
0
Order By: Relevance
“…However, more recent work suggests that assumptions around colormap design, such as the assertion that CIELAB matches perceived differences in data marks [52,54], may not hold in practice. A recent analysis of practices also found that designer colormaps often do not obey conventional guidelines [53]. Empirical evaluations of colormap performance point to conflicting results that often cannot be reconciled with the guidelines [41,42].…”
Section: Approaches To Colormap Designmentioning
confidence: 99%
“…However, more recent work suggests that assumptions around colormap design, such as the assertion that CIELAB matches perceived differences in data marks [52,54], may not hold in practice. A recent analysis of practices also found that designer colormaps often do not obey conventional guidelines [53]. Empirical evaluations of colormap performance point to conflicting results that often cannot be reconciled with the guidelines [41,42].…”
Section: Approaches To Colormap Designmentioning
confidence: 99%
“…Many designer color tools, such as ColorBrewer, generate color ramps that transverse nonlinear paths through the perceptual color space Cyclical noise of 0 means the simulated data contained only random noise. (Smart et al, 2020). The diverging red-blue color palette used here is symmetrical, meaning that there is an equal number of colors on either side of the midpoint.…”
Section: Stimuli and Apparatusmentioning
confidence: 99%
“…We selected a set of 6 colormaps for our experiments representing various designs (see Figure 2). We first started with a corpus of 235 color scales that were collected from a variety of sources by Smart et al [SWS19]. We then selected three colormap pairs with increasing degrees of name variation and, by extension, increasing levels Curves show the running name salience (blue) and name distance (red) measurements across the scale.…”
Section: Colormap Selectionmentioning
confidence: 99%